NIMBY is beautiful : cases of local activism and environmental innovation around the world - Hager, Carol J., 1958-; Haddad, Mary Alice, 1973- (Berghahn Books, 2015)
NIMBY (Not In My Back Yard) protests are often criticized as parochial and short-lived, generating no lasting influence on broader processes related to environmental politics. This volume offers a different perspective. Drawing on cases from around the globe, it demonstrates that NIMBY protests, although always arising from a local concern in a particular community, often result in broader political, social, and technological change. Chapters include cases from Europe, North America, and Asia, engaging with the full political spectrum from established democracies to non-democratic countries. Regardless of political setting, NIMBY movements can have a positive and proactive role in generating innovative solutions to local as well as transnational environmental issues. Furthermore, those solutions are now serving as models for communities and countries around the world.